Global Diversification, Industrial Diversification, and Firm Value - Denis, David J.; Denis, Diane K.; Yost, Keven (Journal of Finance, 2002)
ABSTRACT Using a sample of 44,288 firm‐ears between 1984 and 1997, we document an increase in the extent of global diversification over time. This trend does not reflect a substitution of global for industrial diversification. We also find that global diversification results in average valuation discounts of approximately the same magnitude as those for industrial diversification. Analysis of the changes in excess value associated with changes in diversification reveals that increases in global diversification reduce excess value, while reductions in global diversification increase excess value. These findings support the view that the costs of global diversification outweigh the benefits.